Cytotoxicity of Taxillus tomentosus and Spilanthes calva in Different Cancer Cell Cultures In Vitro (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Cancer is one of the leading diseases to cause death globally. Most of the synthetic drugs used to treat cancer are having serious side effects. So, there is a need to develop the drugs which are used to treat cancer with little side effects. This can led to investigate the plant products having less side effects, for their anticancer activity. The present investigation evaluated the in vitro toxicity of leaf extracts and fractions of Spilanthes calva and Taxillus tomentosus in 5 totally different neoplastic cell cultures, like HeLa (cervical cancer cells), HEK 293 (kidney cancer cells), MCF-7 (breast cancer cells), A549 (lung cancer cells) and Hep G2 (hepatic cancer cells) by 3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and lactate dehydrogenase (LDH) release assays. Among all the test extracts and fractions, petroleum ether and n-hexane fractions of Spilanthes calva, and ethyl acetate and n-hexane fractions of Taxillus tomentosus have been shown maximal cytotoxic activities against all tested cell cultures. The IC50 values of SCPEF, SCNHF and TTEAF were found to be 41.79, 42.26 and 41.01 µg/mL on HEK 293 cells, which were very close to standard drug PCTXL has been found to be 35.22 µg/mL on HEK 293 kidney cancer cells. The TTNHF IC50 value was found to be 39.29 µg/mL which is comparable with the standard PCTXL 39.18 µg/mL on A549 lung cancer cells.